Kebutuhan dan perawatan anak penyandang cerebral palsy yang mengalami drooling: studi eksplorasi - Andri Kenti Gayatina; Fitri Haryanti; Elisabeth Siti Herini (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Needs and care for cerebral palsy children with drooling: an exploratory study Purpose: To explore the needs and care and expectations of parents of children with disabilities that improve saliva.Methods: A qualitative research with a phenomenology conducted at YPAC Semarang in September 2016. Data were collected using in-depth interviews with 6 maternal participants who were selected through purposive sampling and 1 doctor improving medical and 1 teacher as a triangulation participant. Data analysis was performed according to Collaizi's steps.Results: This study produced ten themes, namely: the need to deal with saliva; overcoming feelings of sadness, shame, brokenness, low self-esteem, hurt, sensitive, offended when the child is humiliated, can not bear, feelings of rejection, not accept, afraid and violate themselves; Overcoming the shame of children; Budget for pediatric therapy; strength, enthusiasm, gratitude, patience and endeavor; accepted by the community and considered by the government; Environmental modification; efforts to overcome saliva; poor understanding of mothers; expectation of the mother towards the foundation and the government regarding health services, education, and children's independence.Conclusions: Optimizing the fulfillment of needs and care for CP children who increase the saliva of class IV and V by overcoming saliva using a saliva absorber and prolonging treatment.